Stress performance of embedded carbon fiber reinforced plastics plate consolidated reinforced concrete structure - Hua Zhu (Fracture and Structural Integrity)
With the development of the building industry, various novel building materials have emerged. Modern buildings requires higher on performance of building materials, and the performance of old buildings has not been able to keep up the pace of the times. Extending the service time of old buildings by repairing and reinforcing is inevitable. In this study, 10 reinforced concrete beams including 2 ordinary reinforced concrete beams and 8 carbon fiber reinforced plastics (CFRP) plate reinforced test beams were manufactured. Three-dimensional finite element model was established using finite element software to simulate and compare the stress performance of the strengthening beams with different number of CFRP plate, size, number of groove and shear span ratio. The results demonstrated that the ultimate carrying capacity of the embedded CFRP plate reinforced beams was obviously superior to that of the ordinary reinforced concrete beams; two plates and two grooves were appropriate; the larger the shear span ratio, the better the bearing performance and the smaller the deformation. CFRP plate consolidated reinforced concrete can effectively stabilize buildings which need repairing and reinforcement.